Fecal carriage of extended-spectrum beta-lactamase-producing Enterobacterales in healthy Spanish schoolchildren - López-Siles, Mireia; Moure, Zaira; Muadica, Aly Salimo; Sánchez, Sergio; Cruces, Raquel; Ávila, Alicia; Lara, Noelia; Köster, Pamela Carolina; Dashti, Alejandro; Oteo-Iglesias, Jesús; Carmena, David; McConnell, Michael J. (Frontiers in Microbiology, 2023)
Background: Extended-spectrum ß-lactamase-producing Enterobacterales (ESBL-E) are a serious threat among emerging antibiotic resistant bacteria. The number of cases of ESBL-E infections reported in children has been increasing in recent years, and approved antibiotic treatments for this age group are limited. However, information regarding the prevalence of colonization in European children, factors associated with colonization, and the characteristics of the colonizing strains is scarce. The aims of this study were to determine the prevalence of ESBL-E colonization in faecal samples of apparently healthy schoolchildren, to identify lifestyle routines associated with colonization, and to characterize clonal relationships and mechanisms of resistance in ESBL-E isolates. Methods: A cohort of 887 healthy children (3 to 13 years old) from seven primary and secondary schools in the Madrid metropolitan area was recruited between April-June 2018, and sociodemographic information and daily habits were collected. Faecal samples were screened for ESBL-E carriage in selective medium. ESBL-E isolates were further characterized by assessing molecular epidemiology (PFGE and MLST), ESBL gene carriage, and antibiotic resistance profile. This information was analyzed in conjunction with the metadata of the participants to identify external factors associated with ESBL-E carriage. Results: 24 ESBL-E, all but one Escherichia coli, were detected in 23 children (prevalence: 2.6%; 95% CI: 1.6–3.6%). Of these, seven contained the blaCTX-M-14 allele, five the blaCTX-M-15, five the blaSHV-12, three the blaCTX-M-27, three the blaCTX-M-32, and one the blaCTX-M-9. Significant clonal diversity was observed among the isolates that grouped into 22 distinct clusters (at <85% similarity of PFGE profile). ESBL-producing E. coli isolates belonged to 12 different STs, with ST10 (25%) and ST131 (17%) being the most frequent. Apart from ß-lactams, resistance to trimethoprim/sulfamethoxazole (46%), ciprofloxacin (33%), levofloxacin (33%), tobramycin (21%), and gentamicin (8%) were the most frequently detected. Conclusions: The prevalence of ESBL-E in the studied cohort of children is lower than the average colonization rate previously detected in Europe for both children and adults. E. coli was the main ESBL-producing species detected and CTX-M were the most frequently identified ESBLs. High ST diversity suggests polyclonal dissemination. Compared to other STs, ST131 isolates were associated with resistance to various antimicrobials.